Pengembangan Bahan Ajar Berbasis Video Pembelajaran dalam Meningkatkan Motivasi Belajar Siswa di MTs Az-Zubair Pamekasan - Albustomi, Yazid; Zainab, Nurul (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Teaching materials are a crucial component in supporting the optimization of the learning process. The development of video-based teaching materials, commonly implemented during the learning process, has a significant impact, particularly in fostering enthusiasm and enhancing students' learning motivation. This research aims to develop and test the effectiveness of video-based teaching materials in improving students' learning motivation in Fiqh lessons in class 1 at Mts Az-Zubair Pamekasan. The Research And Development (R & D) method is employed, utilizing data collection techniques such as observation, interviews, and student response questionnaires. The study results indicate that two expert assessments give an average score of 3 with a good category regarding the development of video-based learning materials. Referencing the questionnaire results, it is observed that 90% of students are highly satisfied with the use of video learning in their learning process. Consequently, based on these findings, it can be concluded that video-based learning materials implemented in Fiqh lessons are deemed suitable for further development as an alternative to enhance students' learning motivation.